Red Light-Independent Instability of Oat Phytochrome mRNA in Vivo. - Seeley, KA (1992)
Phytochrome A (phyA) mRNA abundance decreased rapidly in total RNA samples isolated from 4-day-old etiolated oat seedlings following a red light pulse. Putative in vivo phyA mRNA degradation products were detectable both before and after red light treatment. Cordycepin-treated coleoptiles were unable to accumulate the chlorophyll a/b-binding protein mRNA in response to red light, indicating that cordycepin effectively inhibited mRNA synthesis. In cordycepin-treated coleoptiles, phyA mRNA rapidly decreased in abundance, consistent with the hypothesis that phyA mRNA is inherently unstable, rather than being destabilized after red light treatment of etiolated oat seedlings.